1995
DOI: 10.1172/jci117899
|View full text |Cite
|
Sign up to set email alerts
|

The expression of tumor necrosis factor in human adipose tissue. Regulation by obesity, weight loss, and relationship to lipoprotein lipase.

Abstract: A previous study reported the increased expression of the cytokine TNF in the adipose tissue of genetically obese rodents. To examine this paradigm in humans, we studied TNF expression in lean, obese, and reduced-obese human subjects. TNF mRNA was demonstrated in human adipocytes and adipose tissue by Northern blotting and PCR. TNF protein was quantitated by Western blotting and ELISA in both adipose tissue and the medium surrounding adipose tissue. Using quantitative reverse transcriptase PCR (RT-PCR), TNF mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

52
703
3
42

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,172 publications
(800 citation statements)
references
References 59 publications
52
703
3
42
Order By: Relevance
“…The recent finding that adipose tissue is an active endocrine organ and produces several inflammatory mediators provided a unifying mechanism for the linkage between the incidences of chronic diseases. The most abundant protein in adipose tissue is adiponectin, which stimulates immune cells to produce anti-inflammatory cytokines and may explain disturbed immune function in severely obese individuals (4,5) ; adipose tissue has also been shown to overproduce TNFa and IL-6 in obesity (6)(7)(8)(9) . Obesity is associated with a steady infiltration of macrophages into adipose tissue such that in grossly obese individuals, macrophages constitute up to 40% of the cellular population of the tissue (10) .…”
Section: Influence Of Adipose Tissue Mass On Inflammatory Stressmentioning
confidence: 99%
“…The recent finding that adipose tissue is an active endocrine organ and produces several inflammatory mediators provided a unifying mechanism for the linkage between the incidences of chronic diseases. The most abundant protein in adipose tissue is adiponectin, which stimulates immune cells to produce anti-inflammatory cytokines and may explain disturbed immune function in severely obese individuals (4,5) ; adipose tissue has also been shown to overproduce TNFa and IL-6 in obesity (6)(7)(8)(9) . Obesity is associated with a steady infiltration of macrophages into adipose tissue such that in grossly obese individuals, macrophages constitute up to 40% of the cellular population of the tissue (10) .…”
Section: Influence Of Adipose Tissue Mass On Inflammatory Stressmentioning
confidence: 99%
“…Adipose tissue is currently held to be the greatest source of circulating TNF-α, as well as of other endocrine mediators, collectively referred to as 'adipokines'. Likewise, plasma TNF-α levels have been shown to correlate directly with body fat mass [36]. TNF-α modulates insulin action by promoting serine-phosphorylation of IRS-1, which leads to the downregulation of IRS-1 signalling (Figure 3) [37,38], an effect similar to that of FFA.…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 97%
“…It affects insulin resistance via two major mechanisms, inhibition of insulin receptor signalling [3] and down-regulation of the GLUT4 glucose transporter [4]. This was thought to occur via the actions of adipose-derived TNF-α, through autocrine mechanisms in adipose tissue and paracrine effects on skeletal muscle [5]. Indeed, TNF-α levels are higher in the adipose tissue of obese and insulin-resistant rodents and humans than in healthy animals or individuals [1,2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This was thought to occur via the actions of adipose-derived TNF-α, through autocrine mechanisms in adipose tissue and paracrine effects on skeletal muscle [5]. Indeed, TNF-α levels are higher in the adipose tissue of obese and insulin-resistant rodents and humans than in healthy animals or individuals [1,2,5,6]. More recently it has been shown that TNF-α is also expressed in skeletal muscle and that levels are four-fold higher in insulin-resistant, obese humans than in healthy humans [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation